INTEGRASI PENDIDIKAN KARAKTER (PILAR KEMANDIRIAN) DALAM BIMBINGAN DAN KONSELING DI MI - Ihda A’yunil Khotimah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
Character education needs to color every level of education from pre-school to tertiary education even in environments where individuals interact and communicate, because the environment will greatly affect a person's personality, even the theory of transformation says that it is the environment that shapes a person's personality more than genetics (heredity). . The method in this study is a literature review that discusses the importance of integrating character education into counseling guidance. So that the implementation of guidance and counseling in schools can actually be carried out in several forms, not only in a separate room with formal treatment but a counselor/teacher/classroom teacher needs to know the personality and psychology of children who are in need of help. It may require self-service and may also require other people or groups to complete it.